Association between early life exposure to indoor environmental factors and childhood asthma. (December 2022) - Lu, Chan; Liao, Hongsen; Liu, Zijing; Yang, Wenhui; Liu, Qin; Li, Qin
Abstract: Background: Asthma is one of the most common chronic diseases among childhood worldwide, with a rapid increase in developing countries over past decades. Although increasing evidence have linked asthma with indoor environments, their role in early life on asthma development is unclear. Objective: We aim to investigate the association between childhood doctor-diagnosed asthma (DDA) and indoor environmental exposure in four important time windows across lifetime. Methods: We conducted a retrospective cohort study with 8689 children in Changsha, China during 2019–2020. Every child's health condition and home environments were collected by our questionnaire. The time windows of indoor air pollution (IAP) and allergens at home included 1 year before pregnancy, pregnancy, the 1st year after birth, and 1 year before filling in the questionnaire. We used multiple logistic regression models to analyse the associations. Results: We found that exposure to indoor dampness related allergen including mold/damp stains and mold/damp clothes or bedding during four windows were significantly associated with an increased risk of childhood DDA. Childhood DDA was also related with smoke related IAP in pregnancy, 1st year, and past year and renovation related IAP including new furniture and redecoration in pregnancy with ORs (95% CI) = 1.53 (1.12–2.09) and 1.47 (1.02–2.12) after adjusting for covariates and outdoor air pollution and temperature. Pregnancy was identified as the critical time window in home environmental exposure for asthma development, especially for exposure to environmental tobacco smoke (ETS), new furniture, and mold/damp clothes and bedding, with ORs (95% CI) = 1.39 (1.00–1.93), 1.50 (1.09, 2.06), and 1.55 (1.01–2.38). Some specific subjects were more sensitive to the effect of home environments on asthma. Conclusion: This study indicates that exposure to indoor air pollution and allergens in early life plays an important role in the development of childhood asthma, supporting a hypothesis of "(pre-)fetal origin of childhood asthma". Graphical abstract: Image 1 Highlights: Early life exposure to indoor dampness related allergen played a key role in childhood asthma. Smoke related indoor air pollution exposure in whole life increased risk of childhood asthma. Renovation exposure in pregnancy was associated with an increase in childhood asthma. Pregnancy was identified as the critical time window for asthma risk of home environment. Our findings support a hypothesis of "(pre)fetal origin of childhood asthma".